Synthesis and stabilization mechanism of novel stabilizers for fullerene-malonamide derivatives in nitrocellulose-based propellants. (June 2020) - Li, Guang; Jin, Bo; Chai, Zuohu; Liao, Ling; Chu, Shijin; Peng, Rufang
Abstract: Nitrocellulose (NC)-based propellants require stabilizers to avoid early decomposition or even explosion during storage. A series of novel fullerene-malonamide derivatives with different carbon chain lengths on the p -position of the benzene ring was synthesized as stabilizers for NC-based propellants through the Bingel reaction because of the excellent thermal stability and strong ability of these derivatives to eliminate free radicals. The molecular structures of these fullerene-malonamide derivatives were verified via 1 H nuclear magnetic resonance (NMR) spectroscopy, 13 C NMR spectroscopy, Fourier-transform infrared (FT-IR) spectroscopy, ultraviolet–visible spectroscopy, and high-resolution mass spectrometry. Meanwhile, their stability was investigated using methyl violet, vacuum stability, and weight loss tests. Results indicated that the stability of the novel fullerene-malonamide derivatives was considerably better than that of traditional stabilizers, such as N, N′ -dimethyl- N, N′ -diphenylurea and diphenylamine. Moreover, these derivatives exhibited excellent thermal stability at high temperatures. The stability of the fullerene-malonamide derivatives also improved as the carbon chain length on the p -position of the benzene ring on C60 increased. In addition, the stability mechanism of the fullerene-malonamide derivatives was studied through electron paramagnetic resonance spectroscopy, FT-IR spectroscopy, and liquid chromatography-mass spectrometry. Results turned out that the fullerene-malonamide derivatives could react with nitroxide radicals released from the pyrolysis of NC. Hence, these novel fullerene-malonamide derivatives can be used as promising stabilizers for NC-based propellants. Highlights: Six novel fullerene-malonamide stabilizers for nitrocellulose have been designed and synthesized. The molecular structures of fullerene-malonamide stabilizers were confirmed by NMR, FT-IR, UV–vis and HRMS. Stability of fullerene-malonamide stabilizers was better than traditional stabilizers C2 and DPA. Stability mechanisms of novel fullerene-malonamide stabilizers were studied by EPR, FT-IR and LC-MS. Fullerene-malonamide stabilizers can react with the nitroxide radicals released from NC pyrolysis.